2006
DOI: 10.1680/macr.2006.58.5.289
|View full text |Cite
|
Sign up to set email alerts
|

Influence of steam curing on hardened properties of recycled aggregate concrete

Abstract: The effects of steam curing on the hardened properties of recycled aggregate concrete were investigated. In this study, two series of concrete mixtures with water/cement ratios of 0 . 55 and 0 . 45 were prepared. Recycled aggregates were used as 0, 20, 50 and 100% by volume replacements of natural coarse aggregate in the concrete mixtures. The concrete specimens underwent standard water-curing and steam-curing regimes. The test results showed that the strength of concrete decreased as the recycled aggregate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Humidity and temperature are key factors on shrinkage development leading to higher drying shrinkage when humidity lessens, or greater shrinkage at high temperatures (85). Additionally, the curing process may reduce the concrete strain due to shrinkage (86,87). In a recent research, Hanif et al (88) reported that the use of recycled aggregates with high early strength cement and steam curing method led to an improvement of shrinkage performance, lowering early-age cracking.…”
Section: Shrinkagementioning
confidence: 99%
“…Humidity and temperature are key factors on shrinkage development leading to higher drying shrinkage when humidity lessens, or greater shrinkage at high temperatures (85). Additionally, the curing process may reduce the concrete strain due to shrinkage (86,87). In a recent research, Hanif et al (88) reported that the use of recycled aggregates with high early strength cement and steam curing method led to an improvement of shrinkage performance, lowering early-age cracking.…”
Section: Shrinkagementioning
confidence: 99%
“…Kou et al 50 and Poon et al 57 studied the effect of applying a steam curing regime to specimens with increasing coarse RCA content. Steam-cured specimens showed an average of 20% and 30% less chloride ion penetration at 28 and 90 days, respectively, than mixes subjected to standard curing.…”
Section: Exposure To Different Curing Conditionsmentioning
confidence: 99%
“…Furthermore, according to Piaw 119 , the coefficients of correlation (R) show that there is a very strong correlation between the two variables. A similar analysis ( Figure 6) was performed with the total charge passed of RAC mixes produced with binder equivalent to CEM I 27 , based on 123 measurements sourced from 16 publications 44,46,[50][51][52][53][54]57,59,60,[75][76][77]81,82,87 . As in Figure 4, factors related to the use of RA in concrete, known to have a significant influence on the resistance to chloride ion penetration, appear to have had marginal effect on the relationship between the total charge passed and compressive strength.…”
Section: Metakaolinmentioning
confidence: 99%
“…Consequently the mechanical and durability properties of recycled aggregate concrete are considerably lower than the normal concrete particularly at 100% recycled coarse aggregate. At 100% recycled coarse aggregate, the compressive strength of RAC is lowered by 17–30%; 15–45% lower by modulus of elasticity; 7–26% by split tensile strength, and 5–29% by flexural strength . The variation in the results of RAC is mainly attributed to the adherence of quality and quantity of old mortar to the recycled coarse aggregate.…”
Section: Introductionmentioning
confidence: 98%